Phenotypic and genotypic characterization of carbapenemases in carbapenem-resistant gram-negative bacilli isolated from adult cancer patients. - Dalia El.Nobi; Sherein Elgendy; Rania Bakry; Abeer Hassan; Ehsan El-Sabaa (Microbes and Infectious Diseases, 2023)
Background: Carbapenem-resistant Gram-negative bacteria (CR-GNB) infections are prevalent in cancer patients with weakened immune systems, causing significant morbidity and mortality. The empirical use of antimicrobials has reduced mortality but led to the emergence of multidrug-resistant (MDR) bacteria. In this study, identification and susceptibility testing were carried out using standard procedures (Kirby-Bauer and broth microdilution techniques), and phenotypic and genotypic detection of carbapenemase-producing GNB isolated from adult cancer patients was performed using conventional procedures. Methods: One hundred and eight Gram-negative bacteria were recovered from various specimens, with the most common isolates being, Escherichia (E.) coli (45; 41.7%), followed by Klebsiella spp. (38; 35.2%), Acromobacter spp. (9;8.3%), Acinetobacter (A.) baumannii (5; 4.6%) and others including Enterobacter aerogenes, Raoultella ornithinolytica, Serratia fonticola, Citrobacter brakii, Comamonas testosteroni, Proteus mirabilis (11; 10.2%). Concerningly, 64 of 108 Gram-negative bacterial isolates (59.3%) were MDR. Furthermore, 91 out of 108 GNB isolates (84.3%) revealed a pattern of meropenem resistance using the broth microdilution method, which is a worrying rise in the rate of carbapenem resistance. Following the modified carbapenem inactivation method (mCIM), EDTA carbapenem inactivation method (eCIM), and combined disc test as phenotypic tests for the preliminary screening of carbapenemase producers (CPs), conventional PCR was performed on the 91 extracted DNA (Using 6 common carbapenemase primers). Results: It was found that blaNDM was the most common 60(66%), then blaOXA-48, VIM 47 (51.6%), blaIMP 32(35.2%), blaKPC 20(22.2%), and blaGES 12(13.2%). Conclusion: Based on these results, rapid and precise carbapenemase detection is crucial for clinical care, epidemiological investigations, and infection control.